Pharmacokinetic Interaction of Kratom and Cannabidiol in Male Rats - Erin C. Berthold; Shyam H. Kamble; Siva Rama Raju Kanumuri; Michelle A. Kuntz; Alexandria S. Senetra; Yi-Hua Chiang; Sushobhan Mukhopadhyay; Christopher R. McCurdy; Abhisheak Sharma (MDPI AG, 2024)
Kratom and cannabidiol products are used to self-treat a variety of conditions, including anxiety and pain, and to elevate mood. Research into the individual pharmacokinetic properties of commercially available kratom and cannabidiol products has been performed, but there are no studies on coadministration of these products. Surveys of individuals with kratom use history indicate that cannabidiol use is one of the strongest predictors of both lifetime and past month kratom use. The purpose of this study was to determine if there are changes in pharmacokinetic properties when commercially available kratom and cannabidiol products are administered concomitantly. It was found that with concomitant administration of cannabidiol, there was a 2.8-fold increase in the exposure of the most abundant kratom alkaloid, mitragynine, and increases in the exposure of other minor alkaloids. The results of this work suggest that with cannabidiol coadministration, the effects of kratom may be both delayed and increased due to a delay in time to reach maximum plasma concentration and higher systemic exposure of the psychoactive alkaloids found in kratom.